Ferroelectric thin films: basic properties and device physics for memory applications - Okuyama, M; Ishibashi, Y (Topics in Applied Physics, 2000)
Ferroelectric thin films continue to attract much attention due to their developing applications in memory devices, FeRAM, infrared sensors, piezoelectric sensors and actuators. This book, aimed at students, researchers and developers, gives detailed information about the basic properties of these materials and the associated device physics. The contributing authors are acknowledged experts in the field.